Peningkatan Literasi Bela Negara Pada Generasi Muda Era 5.0 - Hesti Rosdiana; Nurmasari Situmeang; R. Maisa Yudono; Lia Wulandari (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This article describes community service activities carried out at PKBM Negeri 34. This community service activity was carried out as an effort to increase state defense literacy in the 5.0 era. This community service activity was carried out using the method of playing short videos, lectures and interactive discussions about state defense. The result of this activity is the growth of awareness of state defense among the younger generation and increasing understanding of state defense and the implementation of state defense values in the younger generation in the 5.0 era.